2020
DOI: 10.1590/1678-4324-2020190351
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality of Chia (Salvia hispanica), Sesame (Sesamum indicum), and Quinoa (Chenopodium quinoa) Oils

Abstract: Each year, the consumption of vegetable oils increases gradually. Some oils, such as chia, sesame, and quinoa, are consumed due to the nutritional properties and health promoters that have been recognized in their components. Based on this premise, the present study aimed to characterize chia (Salvia hispanica), sesame (Sesamum inducum), and quinoa (Chenopodium quinoa) oils, in order to enable their applications in the development of new food products. Chia oil presented higher degradation, as it stood out wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…The low acidity obtained for chia oil is an indication that the triacylglycerols present have not been hydrolysed. These findings are in similar to those observed in cold-pressed chia oil (Martínez et al, 2012), the value of acidity (as oleic acid) was 0.49%, much lower than the maximum values established by Clara et al (2020). Acidity measures the percentage content of free fatty acids in a given amount of oil.…”
Section: Chemical Properties Of the Extracted Chia And Moringa Seed O...supporting
confidence: 89%
“…The low acidity obtained for chia oil is an indication that the triacylglycerols present have not been hydrolysed. These findings are in similar to those observed in cold-pressed chia oil (Martínez et al, 2012), the value of acidity (as oleic acid) was 0.49%, much lower than the maximum values established by Clara et al (2020). Acidity measures the percentage content of free fatty acids in a given amount of oil.…”
Section: Chemical Properties Of the Extracted Chia And Moringa Seed O...supporting
confidence: 89%
“…[11,21] The next stage, where PV starts to increase, can be ascribed to the propagation phase of hydroperoxides. [22] According to Fortuna Clara, [23] chia oil contains natural antioxidants such as carotenoids (5 ppm), polyphenols (140 ppm), and tocopherols (103 ppm), but these compounds appeared insufficient to protect the oil during storage at 25 • C (Figure 2B and B). However, when CO was blended with just one commercial antioxidant rich source (VE, BC or ASX), a better protection against oil oxidation was observed, as PV did not exceed 3 meq O 2 kg -1 at the end of the experiment, being the CO/BC blend the one that showed the lowest PV, followed by CO/ASX and finally CO/VE.…”
Section: Resultsmentioning
confidence: 99%
“…CO naturally contains carotenoids (5 ppm) and tocopherols (102 ppm), [ 43 ] but these natural antioxidants were not enough to protect the oil when storing microcapsules at 30°C. However, the addition of 2000 ppm VE or ASX, respectively, from commercial edible antioxidant sources, significantly contributed to decrease oxidative deterioration (Figure 4) possibly due to a synergistic effect of the naturally occurring antioxidants and VE or ASX added to the formulations.…”
Section: Resultsmentioning
confidence: 99%
“…But when storing these powders at higher temperatures (30 • C), antioxidants seem to have played a fundamental role against oxidative deterioration. CO naturally contains carotenoids (5 ppm) and tocopherols (102 ppm), [43] but these natural antioxidants were not enough to protect the oil when storing microcapsules at 30 • C. However, the addition of 2000 ppm VE or ASX, respectively, from commercial edible antioxidant sources, significantly contributed to decrease oxidative deterioration (Figure 4) possibly due to a synergistic effect of the naturally occurring antioxidants and VE or ASX added to the formulations. Conversely, Espinaco et al [13] found that the addition of ASX or VE to CO promoted higher PV than those observed for CO alone when storing at 25 and 45 • C. In this case, they added antioxidants to CO at lower concentrations (400 ppm) than those used in our work (2000 ppm).…”
Section: Oxidative Stability Of Microencapsulated Chia Oilmentioning
confidence: 99%